UDC 338.23 INNOVATIVE ACTIVITY OF BUSINESS ENTITIES IN THE CONDITIONS OF TRANSFORMATION: A RETROSPECTIVE ANALYSIS: - - Kurpayanidi, Konstantin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. To conduct a theoretical analysis of the categories "innovation" and "innovative activity". To prove, from the standpoint of historical dialectics, that innovation is an endogenous source of economic growth. Methods. The study used a systematic approach, retrospective analysis, abstract-logical analysis, grouping, comparison, factor analysis. Results. In the current conditions of instability of the world economy, the issue of its further development, including from a technological point of view, is relevant. In historical retrospect, the emergence of technological innovations on the market had a positive impact on the process considered in the study. The recognition of innovation as an endogenous source of economic growth is due to the nature of the post-industrial economic structure, characterized by the decline in the role of traditional factors of production in the formation of competitive advantages of individual producers, as well as the formation of a qualitatively new type of progressive macroeconomic dynamics. In these conditions, the innovative activity of business entities becomes particularly relevant. The article considers various approaches of scientists and representatives of various economic schools to the definition of the concepts of "innovation" and "innovative activity". Conclusion. Based on a retrospective analysis of a number of scientific papers devoted to innovation, it is concluded that in order to ensure the successful and dynamic development of an enterprise producing high-tech products, it is necessary first of all to widely apply various methods of innovation management, which should include simultaneous and coordinated use of technological, scientific, personnel, commercial and other policies that provide a systematic solution to the problems of innovative development.